Health insurance benefit design and healthcare utilization in northern rural China. - Hong Wang; Yu Liu; Yan Zhu; Lei Xue; Martha Dale; Heather Sipsma; Elizabeth Bradley (PLoS ONE)
Background Poverty due to illness has become a substantial social problem in rural China since the collapse of the rural Cooperative Medical System in the early 1980s. Although the Chinese government introduced the New Rural Cooperative Medical Schemes (NRCMS) in 2003, the associations between different health insurance benefit package designs and healthcare utilization remain largely unknown. Accordingly, we sought to examine the impact of health insurance benefit design on health care utilization. Methods and findings We conducted a cross-sectional study using data from a household survey of 15,698 members of 4,209 randomly-selected households in 7 provinces, which were representative of the provinces along the north side of the Yellow River. Interviews were conducted face-to-face and in Mandarin. Our analytic sample included 9,762 respondents from 2,642 households. In each household, respondents indicated the type of health insurance benefit that the household had (coverage for inpatient care only or coverage for both inpatient and outpatient care) and the number of outpatient visits in the 30 days preceding the interview and the number of hospitalizations in the 365 days preceding the household interview. People who had both outpatient and inpatient coverage compared with inpatient coverage only had significantly more village-level outpatient visits, township-level outpatient visits, and total outpatient visits. Furthermore, the increased utilization of township and village-level outpatient care was experienced disproportionately by people who were poorer, whereas the increased inpatient utilization overall and at the county level was experienced disproportionately by people who were richer. Conclusion The evidence from this study indicates that the design of health insurance benefits is an important policy tool that can affect the health services utilization and socioeconomic equity in service use at different levels. Without careful design, health insurance may not benefit those who are most in need of financial protection from health services expenses.